Pengaruh Viral Marketing Dan Fasilitas Wisata Terhadap Minat Bekunjung Ke Pantai Minang Rua Lampung Selatan - Ramayanti, Ria; Saodin, Saodin (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to examine the Influence of Viral Marketing and Tourism Facilities on Interest in Visiting Minang Rua Beach, South Lampung. This research was conducted at Minang Rua Beach with the address Jl Pariwisata Batu Alif Dusun Kelawi 1 Kelawi Village, Bakauheni District. The population used in this study was the number of tourists who were interested in visiting the Minang Rua Beach tourist attraction, South Lampung with a sample size of 200 respondents. The sampling technique used was Purposive Sampling. The data analysis technique used validity tests, normality tests, classical assumption tests and multiple regression analysis. The analysis tool used was SPSS ver.26. The results of this study indicate that Viral Marketing and Tourism Facilities have a positive effect on Interest in Visiting Minang Rua Beach, South Lampung, both partially and simultaneously